Singing in Zion : music and song in the life of an Arkansas family - Cochran, Robert, 1943- (University Of Arkansas Press, 1999)
This book is a lyrical exploration of the connection between one family's musical traditions and its rural community of Zion, Arkansas. In 1959, three Gilbert sisters - Alma, Helen, and Phydella - began compiling songs they remembered and sending them to one another in letters. Their tendency to center memory in sound rather than sight reveals an unusual musical birthright. Robert Cochran has constructed a composite portrait of this family for whom music is the center of life. He examines their lived experience as they anchor their history on songs and shows how the singing and playing of musical instruments informed their lives.